Application of Steel Sheet Pile in Deep Foundation Pit Support of Collapsible Loess Regions. Issue 7 (April 2020) - Yang, Yang; Liu, Wanfeng; Hu, Aiping; Li, Fei; Yang, Zhaoqian
Abstract: Due to its high quality, simple construction, good durability and interchangeability, steel sheet pile can reduce the requirements of space for construction tasks and other advantages. In recent years, it has been widely used in support engineering. Taking a deep foundation pit in a collapsible loess area as an example, this paper analyzes the application and calculation of steel sheet pile support under the complex operation conditions, which is composed of many adverse factors such as the limitation of the construction work area's narrow influence on the construction, and expounds the feasibility of steel sheet pile in the deep foundation pit support in collapsible loess area, which adds precious steel sheet pile support to the deep foundation pit in collapsible loess area The experience has a good reference and guiding significance for the use and promotion of steel sheet pile support in similar projects.